Comparison of peppermint and chamomile aromatherapy in reducing emesis gravidarum among first-trimester pregnant women - Nurwianti Nurwianti; Ernita Prima Noviyani; Putri Agus Febriyani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Emesis gravidarum is one of the most common complaints experienced by pregnant women during the first trimester and may affect maternal nutritional status, daily activities, and quality of life. Aromatherapy is a non-pharmacological intervention that is considered safe and easy to apply for reducing nausea and vomiting during pregnancy. Purpose: To determine the effectiveness of peppermint and chamomile aromatherapy in reducing emesis gravidarum in first-trimester pregnant women. Method: This quasi-experimental study used a two-group pretest–posttest design. Forty first-trimester pregnant women with mild nausea and vomiting were assigned to peppermint aromatherapy and chamomile aromatherapy groups. Nausea and vomiting were measured using the Pregnancy-Unique Quantification of Emesis and Nausea questionnaire. Data were analyzed using paired-samples t-tests and independent-samples t-tests. Results: The mean nausea and vomiting score in the peppermint group decreased from 5.55±0.686 to 3.15±0.366 (p < 0.001). In the chamomile group, the mean score decreased from 5.60±0.681 to 3.25±0.444 (p < 0.001). Independent-samples t-test showed a significant difference between the two groups (p < 0.001), indicating that peppermint aromatherapy was more effective than chamomile aromatherapy. Conclusion: Both peppermint and chamomile aromatherapy effectively reduced nausea and vomiting in first-trimester pregnant women, with peppermint showing greater effectiveness. Suggestion: Peppermint aromatherapy may be recommended as a complementary non-pharmacological intervention for managing emesis gravidarum in antenatal care services.